Repensando el modelo de intervención con menores y jóvenes migrantes solos/as : Reflexiones y propuestas desde la experiencia - Herrero Galiano, Eva (Cuadernos de Trabajo Social, 2025)
This paper analyses and questions the model of care and social intervention with unaccompanied migrant minors and young people, based on the analysis of the professional practice of an organisation: XXX. Using qualitative and participatory methodologies, based on individual interviews with professionals and young people, case reviews, discussion groups with young people, documentary analysis, together with a critical account of professional practice, it questions the current welfare and normative model of intervention and presents an alternative based on approaches based on law and participatory methodologies focused on the person. The critical analysis of the conventional models of social intervention applied to such a vulnerable group as minors and young migrants alone in Spain, allows the social sciences linked to social intervention to question their professional practice, enrich it and move towards less normative, more comprehensive and participatory models.